Test the Effectiveness of Mulberry Leaf Extract (Morus Nigra) Against the Inhibitory Power of Pseudomonas Sp. - Anik Latifah; Setiana Andarwulan; Septi Ardiyanti; Miftahul Hakiki (PROFESSIONAL HEALTH JOURNAL, 2024)
Introductions : Urinary Tract Infection (UTI) is one of the impacts caused by the use of IUDs, namely IUDs. The cause of UTI itself is dominated by the presence of microorganisms that infect the urinary tract. Pseudomonas is one of the bacteria that causes the third largest UTI after E. Coli and Enterococcus. Pseudomonas is capable of infecting the urinary tract when it is inserted, besides that the bacteria can also enter due to improper cleaning techniques. Mulberry leaves are believed to have antibacterial properties such as flavonids, tannins, alkaloids and terpenoids, which can inhibit the growth of bacteria. Methods : The method used in this study uses laboratory experimental methods, by measuring the cause and effect of the independent variable on the dependent variable. Using a post-test only control group design approach. Result : The results showed that there was an inhibition zone formed at the smallest concentration of 60% with the medium category of 8,4 mm and the widest inhibition zone was found at a concentration of 100% with the strong category of 12, 6 mm. The results of the analysis test using One Way Anova proved that there was a significant effect of giving mulberry leaf extract on the inhibition of Pseudomonas with a P value of 0.000. Pos Hoc’s test results showed the most influential concentration in each treatment, namely 100%. Conclusions : From the research results, it was found that concentrations of 100% were the most effective concentrations in inhibiting the growth of Pseudomonas bacteria.